2012
DOI: 10.3122/jabfm.2012.06.120021
|View full text |Cite
|
Sign up to set email alerts
|

Association of Speculum Lubrication with Pain and Papanicolaou Test Accuracy

Abstract: Purpose: To determine the effects of lubrication of the vaginal speculum before insertion during a Papanicolaou test on perceived pain and quality of the cytology specimen.Methods: Four hundred eligible women participating in cervical cancer screening and an early detection program were randomized with respect to lubricant gel use before speculum insertion. Perceived pain during speculum insertion and cytology results were assessed in study groups.Results: The mean age of the patients was 45.7 years (range, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 21 publications
(19 reference statements)
3
26
1
2
Order By: Relevance
“…The use of lubricant to facilitate the insertion of vaginal speculum is seen as a way to minimize the pain reported by women during the examination, which contributes to improve adherence to screening and, thereby, decreases the incidence of cervical cancer . However, the use of lubricant in obtaining cervical smears is controversial and criticized by some authors, given the possibility of changing the outcome of cervical cytology, which may produce less reliable results …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of lubricant to facilitate the insertion of vaginal speculum is seen as a way to minimize the pain reported by women during the examination, which contributes to improve adherence to screening and, thereby, decreases the incidence of cervical cancer . However, the use of lubricant in obtaining cervical smears is controversial and criticized by some authors, given the possibility of changing the outcome of cervical cytology, which may produce less reliable results …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the presence of liquid vaseline was not observed in the analyzed slides. Excess of inflammatory cells, large amounts of blood or lack of cells in the slides were considered collection artifacts, considered as unsatisfactory samples in some studies, excluding the hypothesis that overlapping lubricant could alter the interpretation of results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of a small amount of water-based lubricant with speculum examination has been shown to decrease examination discomfort compared with use of water alone (45)(46)(47). Exfoliated cells are collected from the transformation zone of the cervix and transferred to a vial of liquid preservative that is processed in the laboratory (liquidbased technique) or transferred directly to a slide and fixed (conventional technique).…”
Section: Cervical Cytology Screening Techniquesmentioning
confidence: 99%
“…Guler et al 5 completed a large study (400 women) providing more information on the lubrication/no lubrication argument during Papanicolaou smear collection. The bottom line: lubrication was helpful for postmenopausal women but not for premenopausal women.…”
Section: Clinical Managementmentioning
confidence: 99%